Proposta de Procedimento Operacional Padrão (POP) em Terapia ocupacional para uma Unidade de Tratamento de Queimaduras (UTQ) em Sergipe - Menezes, Larissa dos Santos (2021)
Various situations can influence the engagement of occupations, especially those linked to health conditions, such as burns, which are total or partial injuries that cause the annihilation of the epithelial tissue and annexes, which can directly compromise the deeper organs. This study aimed to propose a Standard Operating Procedure (SOP) in Occupational Therapy for a Burn Treatment Unit (UTQ). The methodology used was a qualitative bibliographic research, carried out in national journals available in the BVS database, followed by an exploratory reading of the articles found, with cataloging and compilation of data that were in accordance with the proposed objective, enabling the theoretical foundation for the elaboration structured POP. In the results, 70 articles were found, only five were selected, four of which described procedures performed by Occupational Therapy in hospitals, with patients who suffered burns, and one described the role of the Occupational Therapist in the hospital environment. The discussion was presented from the topics listed in the SOP: general objective, target audience, eligibility criteria, human resources, duration of care, evaluation process in Occupational Therapy, resources/materials, occupational therapy discharge criteria, behaviors and conducts, that were produced from the bibliographic reference research. Considering the research, it was possible to evidence the lack of references that discuss about the use of the SOP, importance, definition and standardization for its creation. The SOP will influence the provision of standardized services that aim to optimize the time of care, offering them with higher quality, aiming at shorter hospital stays and fewer commitments.